O ensino de mando vocal para crianças com Transtorno do Espectro Autista: o efeito do atraso gradual do modelo ecoico - Dib, Rodolfo Ribeiro (2017)
Children with Autism Spectrum Disorder frequently experience delays in their vocal verbal behavior. Previous studies that have attempted to teach verbal mand to autistic children through the scope of Behavior Analysis have used different antecedents in the process of teaching as a means to facilitate and speed up the acquisition of this verbal operant. The present study investigates the effect of gradually delaying the echoic method, until completely removing it to teach vocal mand. Along with the addition of the echoic method, participants were deprived of an item whose topography had been previously taught. The echoic model corresponding to the mand topography taught was immediately repeated by the researcher after putting away the item of interest to the child inside a box and, gradually, the time for presentation of the echoic model was delayed. The intention was to investigate whether the motivating operation alone could control the verbal operant. Three children with Autistic Spectrum Disorder between three and four years old participated in the study. Two participants were taught three vocal mand topographies and one was taught two topographies. One of the participants learned all three mand responses in just a few sessions, while two participants learned only one over the course of additional sessions. At the follow-up session twenty days after being taught the mands, the participants still provided the correct responses. The importance of variables such as motivation, the participants’ starting repertoire, number of attempts, and frequency of the sessions is discussed from the perspective of the study’s efficacy. Limitations such as the lack of planning of a generalization process and the low number of participants should be addressed in future studies